Sosialisasi Peran Keluarga Dan Masyarakat Dalam Mencegah Dispensasi Kawin Akibat Pergaulan Bebas Di Desa Pasiran - Nurmisda Ramayani; Muhammad Iqbal Qalbaini; Mawar; Dea Novita (peduli riset dan pengabdian masyarakat, 2025)
Marriage dispensation is a legal policy that provides an exception to the minimum marriage age requirement as stipulated in Law Number 16 of 2019 concerning marriage. Although it aims to provide solutions in urgent situations, in practice, marriage dispensation is often requested due to premarital relationships that result in out-of-wedlock pregnancies. This phenomenon not only has legal implications but also affects children's physical and mental health, education, and social welfare. The implementation of this study was carried out through socialization and educational sessions for adolescents and the community of Pasiran Village. This activity employed a qualitative descriptive method and direct observation as data collection techniques. The findings indicate that the phenomenon of marriage dispensation due to premarital relationships is a complex issue that requires a comprehensive approach in its resolution. The primary factor driving marriage dispensation requests is teenage pregnancy outside of marriage, which often occurs due to a lack of understanding of reproductive health, weak parental supervision, and a social environment that is permissive toward premarital relationships. The family plays a crucial role in establishing proper parenting patterns, fostering open communication, and instilling moral and religious values in children from an early age. Additionally, society is also expected to contribute by creating a healthy social environment and supporting stricter policies regarding marriage dispensation applications. Through synergy between families, communities, and the government, it is hoped that a conducive environment for children's and adolescents' development can be established, allowing them to grow and develop optimally without being trapped in the negative consequences of early marriage.